2016
DOI: 10.1007/s00415-016-8231-z
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation and attempts in patients with stroke: a population-based study

Abstract: Stroke is known to be associated with an increase in the risk for suicide. However, there are very few population-based studies investigating the risk of suicidal ideation and attempts in patients with stroke. The purpose of this study was to compare the risk of suicidal ideation and attempts between patients with stroke and population without stroke using nationwide survey data. Individual-level data were obtained from 228,735 participants (4560 with stroke and 224,175 without stroke) of the 2013 Korean Commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…All studies were written in English language and were conducted in Brazil,30 Canada,9 21 China,22 31 Finland,26 Hong Kong,27–29 Korea,8 14 24 New Zealand,23 Portugal15 and USA 25. Sample sizes ranged between 7330 and 45608 individuals. Assessment of suicidal ideation was completed at very different points in time after stroke, varying from a few days15 22 24 25 31 to several months,21 23 26–30 using heterogeneous methods including single-item tests, Beck Depression Inventory (BDI), Beck Scale for Suicide Ideation (BSI), General Health Questionnaire (GHQ), Geriatric Mental State Examination (GMS), Hamilton Depression Rating Scale (HDRS), Montgomery Asberg Depression Rating Scale (MADRS), Patient Health Questionnaire (PHQ), Present State Examination (PSE) and Structured Clinical Interview for DSM (SCID).…”
Section: Resultsmentioning
confidence: 99%
“…All studies were written in English language and were conducted in Brazil,30 Canada,9 21 China,22 31 Finland,26 Hong Kong,27–29 Korea,8 14 24 New Zealand,23 Portugal15 and USA 25. Sample sizes ranged between 7330 and 45608 individuals. Assessment of suicidal ideation was completed at very different points in time after stroke, varying from a few days15 22 24 25 31 to several months,21 23 26–30 using heterogeneous methods including single-item tests, Beck Depression Inventory (BDI), Beck Scale for Suicide Ideation (BSI), General Health Questionnaire (GHQ), Geriatric Mental State Examination (GMS), Hamilton Depression Rating Scale (HDRS), Montgomery Asberg Depression Rating Scale (MADRS), Patient Health Questionnaire (PHQ), Present State Examination (PSE) and Structured Clinical Interview for DSM (SCID).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have described an increased risk of suicide among stroke survivors [ 4 , 5 ]. Compared with subjects who had not suffered a stroke, those who had were found to be at increased risk of suicidal ideation and attempted suicide [ 6 ]. Thus, the identification of factors associated with suicidal ideation after stroke is an important clinical and public health issue.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with stroke had a higher risk of attempting suicide (odds ratio: 1.64, 95% CI: 1.21–2.22). 36 Furthermore, we found that the risk of SDO significantly increased with the number of stroke events. Older patients with more than four strokes had the highest cumulative incidence of SDO ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 71%